EFEKTIVITAS PENGGUNAAN METODE IMAGE STREAMING DALAM PEMBELAJARAN MENULIS CERITA PENDEK PADA SISWA KELAS XI SMA DARUL FALAH CIHAMPELAS - Nur Resta Meilasari; Junianto Junianto; Ika Mustika (IKIP Siliwangi, 2018)
This research is based on the researcher's curiosity about the effectiveness of the use of Image Streaming method in learning short story writing in class XI. Aiming to find an increase from the initial value to the final value in short story writing lesson using the method of Image Streaming in class XI. This research begins with the activity of giving the initial test in class XI IPS 2 SMA Darul Falah Cihampelas, then continued with treatment in the form of Image Streaming method in short story writing lesson, and continued giving final test by the researcher to see effectiveness of the method use, data by using descriptive qualitative research methods that describe the results of the value obtained in the field. The results showed that the method of streaming image was effective in learning short story writing, since the average score of the initial test score was 59 and the final test was 80.1, there was a 47% improvement from the initial test to the final test.